Enabling semantic interoperability in multi-centric clinical trials on breast cancer. Issue 3 (March 2015) - Alonso-Calvo, Raul; Perez-Rey, David; Paraiso-Medina, Sergio; Claerhout, Brecht; Hennebert, Philippe; Bucur, Anca
Highlights We present a standard-based semantic interoperability solution. This solution uses a mechanism that exploits semantic normalization over HL7 model. It has been used for testing in trial recruitment or trial feasibility. Execution times obtained in testing empower its utilization for end user tools.